A legal study on Fisheries Act 1985 in addressing the issue of illegal fishing in Malaysian maritime zone / Mohamad Raimi Mohamad Nor - Mohamad Nor, Mohamad Raimi (2018)
The fisheries sector plays a crucial role as a contributor to protein sources, to Gross Domestic Product (GDP), employment, and development of upstream and downstream fishery-based industries. The weaknesses of the Fisheries Act 1985 and regulations that cannot convict the converted cargo vessel involved with illegal fishing (fishing by squid jigging and transferred fish or squid from the local fishing boat) becoming a growing concern as it will be taken advantage by foreigners. Problems arise when a cargo vessel cannot be convicted because it is not categorized as a fishing vessel as provided under any provision of this act. Where, the cargo vessel will proceed under the jurisdiction of the Marine Department of Malaysia. There is an urgent need to improve this act to prevent illegal fishing from stolen of the country's marine revenue. Thus, the effectiveness of this study on the comparison with the Fisheries Management Act 1991 (FMA 1991) from Australia was made to fill the lacunae in law. The purpose of this legal study is to review the effectiveness of the Fisheries Act 1985 and also to compare this act with FMA 1991 for the purpose of improvements to be proposed. It specifically examines the inherent weaknesses (lacunae) in this act that cannot convict the accused. This legal study is based on a doctrinal research, the laws in Malaysia related with illegal fishing by foreign vessel and the current situation of encroachment into Malaysian Maritime Zone were examined and a free flow interview with MMEA person was conducted. The study suggests that some amendments should be made to this Act to ensure that the jurisdiction to investigate and prosecute the converted cargo vessels involved with illegal fishing in the Malaysian Maritime Zone. Hopefully, this study will contribute and add value to efforts to amend this Act towards a powerful and comprehensive act. It is also expected to reduce the encroachment of this type of vessel entered to take the revenue of country's fishery sector.